Greenhouse gas emissions from nontilled, permanent raised, and conventionally tilled beds in the central highlands of Mexico - Dendooven, Luc; Patiño-Zúñiga L; Verhulst, Nele; Boden K; García Gaytán, A.; Luna Guido M; Govaerts, Bram (CRC Press, 2013)
The effects of climate change can already be felt around the world, and they will likely impact all facets of human civilization—from health, livelihood security, agricultural production, and shelter to international trade. Since anthropogenic factors are mainly to blame for the current trends in global warming, human intervention will be necessary to mitigate it. With 17 authoritative chapters, Combating Climate Change: An Agricultural Perspective outlines a framework for preparing agriculture for climate change, presenting the causes and consequences of climate change and possible remediation measures.